Health Risk Assessment of Fluoride Removal from Drinking Water - Abubaker A. Sharif; Nader A. Alaziby; Iman Shenqir; Darine Trabelsi (African Journal of Advanced Pure and Applied Sciences, 2025)
Fluoride is a naturally occurring mineral that can be found in various water sources, including groundwater and surface water. In controlled amounts, fluoride has been proven to have dental benefits, preventing tooth decay and strengthening tooth enamel. Reverse Osmosis (RO) is considered as an effective method used to separate and extract dissolved solids, organics, and bacteria from water. This study aimed to assess the health risks associated with fluoride removal from drinking water in Tripoli, the Capital city of Libya by using purification systems. Forty water samples were collected before and after desalination process different areas of Tripoli. Water Samples (groundwater, water distribution network and desalinated) were coded from 1 to 20 based on the source type. Samples were analyzed using DR3900 Laboratory VIS Spectrophotometer. Mean difference concentration of fluoride in the collected baseline water samples (before RO filtration) were found to vary between 0.08 and 1.16 mg/L. All of the water samples showed a complete reduction in fluoride content by 100% after passing through various RO filters. The results of the study showed that the use of reverse osmosis water filtration technologies has a substantial effect in reducing the fluoride levels in drinking water within unacceptable limits set by the World Health Organization (WHO) and the Environmental Protection Agency (EPA).